Analysis of the Effect of Servant Leadership Style on Loyalty Through Empowerment - Mohzana Mohzana; Siti Yumnah; Nurhuda Nurhuda; Sutrisno Sutrisno; Nafiul Huda (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2023)
This study aims to: 1) Test and analyze whether Servant Leadership Style has an effect on loyalty, and will be answered through questionnaires distributed to respondents and then tested with several tests offered to determine the effect of these variables. 2) Test and analyze whether empowerment has an effect on loyalty, and will be answered by processing data by conducting several tests to determine the effect of these variables 3) Testing and analyzing whether Servant Leadership Style has an effect on loyalty through empowerment, and will be answered by processing respondent data through several The test is used to find out whether Servant Leadership Style has an effect on loyalty, or the empowerment variable has more influence on loyalty. The research method uses a quantitative approach that explores each variable and tests hypotheses using a structural equation model. The results showed that the overall hypothesis tested has a positive and significant value. Servant Leadership on Loyalty through empowerment has a fairly good value and can be said to have a positive and significant effect. This shows that the empowerment variable as an intervening variable can contribute to fostering loyalty to members.